Manajemen Layanan Khusus di MTs Negeri 4 Kulon Progo - Sulistya, Heru (Jurnal Pendidikan Madrasah, 2024)
This study aims to explore and describe the special services available in MTs Negeri 4 Kulon Progo including library, health, counselling guidance, and security services as an integral part of the education management component. This study uses a qualitative method with a descriptive analysis approach. Data was collected through interviews, observations, and documentation. The results of the study show that, first, library services at MTs Negeri 4 Kulon Progo are managed by adopting management functions, including planning, procurement, inventory, use, maintenance, smelting, and development. Both health services are carried out guided by the Trias UKS program, including health education, health services, and fostering a healthy environment for madrasas. The three guidance and counselling services are carried out by Guidance and Counselling (BK) teachers by focusing on four, namely personal, learning, social, and career services. Fourth, security services focus on guarding madrasah assets in the form of valuables, facilities and infrastructure. Security services are also carried out by providing safety assistance for all madrasah residents when entering the madrasah environment.